REDUCTION OF POSTOPERATIVE WOUND INFECTION AFTER APPENDECTOMY BY PERITONEAL CLOSURE AND WOUND IRRIGATION WITH NORMAL SALINE - Ahmad Jaleel Abdul-Razzak; Zeki A Al-Faddagh (Basrah Journal of Surgery, 2012)
The most common complication following appendectomy is postoperative wound infection and since it has major effects on patient’s health & recovery and on the health system as it consumes time and essential resources so from this fact came the importance of the researches that are done to find any means to reduce postoperative wound infection and many of them have been shown to be beneficial in reducing wound infection like the use of prophylactic antibiotics, postoperative antibiotics and laparoscopic appendectomy but in this study we look for the effectiveness of 2 simple measures which are peritoneal closure and wound irrigation with normal saline in reducing the incidence of postoperative wound infection. Aim of the study: to know if peritoneal closure and wound irrigation with normal saline would significantly reduce the incidence of postoperative wound infection after appendectomy. The study had been carried out from January 2010 to January 2012 in Al-Mawanee General Hospital and it had been done by the same surgeon and as emergency cases. The study included 297 patients divided into: The control group: include those in whom no peritoneal closure and no wound irrigation were done, patients in this group were 153. Case group: include those in whom peritoneal closure and wound irrigation with normal saline had been done and it included 144 patients. Comparison between the two groups had been done according to sex, age, and the state of inflammation of the appendix also factors affecting wound healing and increasing the incidence of wound infection had been taken in consideration. Data were analyzed using P value to determine the significance of the results. Although the incidence of acute appendicitis was slightly higher in males but the incidence of wound infection was found to be higher in females but it was not statistically different so sex is not a risk factor for the development of wound infection in both groups. Regarding age, in both control and case groups, the highest rate of incidence of acute appendicitis was in the age group 21-40 years but the highest rate of wound infection was in the age group 60 years and above, it was 50% in control group and 16% in the case group and so age is a risk factor for the development of wound infection and there is a clear reduction in the incidence of wound infection after the use of peritoneal closure and wound irrigation with normal saline and there were also reduction in the incidence of wound infection in all other age groups after using these two measures. Regarding the state of severity of inflammation of the appendix the highest rate of wound infection was found in the severe appendicitis subgroup in both the control (infection rate was 31.4%) and case (9.6%) groups but again there was a clear reduction in the incidence of wound infection. In conclusion: peritoneal closure and wound irrigation with normal saline help in reducing the incidence of postoperative wound infection after appendectomy.